Al-Ghazali's Perspective on Intellect: Its Role and Potential in Achieving Insān Kāmil - Nabila Huringiin; Nur Hamidah (Journal of Islamic and Occidental Studies, 2025)
In Islamic intellectual history, intellect (‘aql) is not merely a cognitive faculty but a moral and spiritual instrument. However, contemporary discourse often reduces reason to technical rationality, neglecting its ethical and transcendent dimensions. This article examines al-Ghazali’s understanding of intellect and its role in guiding human beings toward insān kāmil (the perfect human). The study adopts a qualitative library-based methodology, employing descriptive and analytical approaches. Primary sources include al-Ghazali’s key works, notably Iḥyā’ ‘Ulūm al-Dīn and al-Munqidz min al-Dhalāl complemented by classical and contemporary scholarly interpretations. The analysis focuses on al-Ghazali’s classifications of intellect, its epistemological scope, and its relationship with revelation and spiritual practice. The findings show that al-Ghazali conceives intellect as a divine light residing in the heart and functioning as the primary source of knowledge. He distinguishes intellect into practical and theoretical types and outlines hierarchical stages culminating in the acquired intellect (al-‘aql al-mustafād). Intellect is inseparable from revelation and moral discipline, as ultimate truth transcends sensory and rational limits and requires spiritual illumination. When harmonized with faith and ethical practice, intellect guides humans toward spiritual maturity, moral excellence, and social responsibility. The study concludes that al-Ghazali’s integrated vision of intellect offers a normative model for achieving insān kāmil and remains relevant for addressing contemporary intellectual and moral challenges.